Letter from the Editors-in-Chief - Sisodia Wadhwa, Mrinalini; Lee, Suan (The Columbia Journal of Asia, 2022)
Letter from Mrinalini Sisodia Wadhwa and Suan Lee, Editors-in-Chief of Volume I, Issue 1 and Co-Founders of the Columbia Journal of Asia.